On non-violence and compassion - Inamdar, Satish; Gandhi, Mohandas Karamchand; Bstan-vdzin-rgya-mtsho, Dalai Lama XIV. (Dept. of Information and International Relations, Central Tibetan Administration, 2005)
Selections from the works of Mahatma Gandhi and His Holiness the Dalai Lama